Gods of “Second Modernity”: Religion and Spirituality from Ulrich Beck’s Sociological Perspective - Camorrino, Antonio (Italian Sociological Review, 2022)
This paper aims to deepen Ulrich Beck’s contribution to the analysis of the religious dimension in contemporary society within the broader theorization of the “risk society”.To this end, I briefly discuss the question of desecularization in the introductory section. In the second I outline in a very synthetic way the distinctive features of religion and the new forms of spirituality, suggesting a possible defining line of demarcation between the two phenomena starting from the different relationship with the transcendence that these two phenomena have. In the third, I summarize the main characteristics of the “risk society”, those that in my opinion are most closely linked to the desecularization process. In the fourth, instead, I analyze what I consider Ulrich Beck’s greatest contribution to the sociology of religion, highlighting some similarities and differences with other previous theories and, therefore, his original contribution. In the conclusions I summarize the results of the reasoning, motivating why Beck’s theory about “a God of one’s own” is a useful conceptualization capable of shedding light both on the phenomenon of religion and new forms of spirituality in the “risk society”.